2018
DOI: 10.1002/jcb.26607
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐4 induces a CD44high/CD49bhigh PC3 subpopulation with tumor‐initiating characteristics

Abstract: Pro‐ and anti‐inflammatory cytokines may influence proliferation, migration, invasion, and other cellular events of prostate cancer (PCa) cells. The hyaluronan receptor CD44, which is regulated by Interleukin (IL)‐4, is a prostate basal cell marker. CD44high/CD49bhigh expressing cells have been demonstrated to have tumor‐initiating characteristics. Here, we aimed to analyze the effects of long‐term IL‐4 treatment on CD44/CD49b expression, migration, proliferation, and clonogenic potential of basal‐like PCa cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The different phenotype, based on CD44 gene expression in PC3 and DU145 cells, was confirmed by a different response to IL-4, a regulator of basal-like cells showing characteristics of tumor-initiating cells by inducing expression of CD44. In fact, it was reported that IL-4 administration strongly induces CD44 expression in PC3, but not in DU145 cells [74].…”
Section: Discussionmentioning
confidence: 99%
“…The different phenotype, based on CD44 gene expression in PC3 and DU145 cells, was confirmed by a different response to IL-4, a regulator of basal-like cells showing characteristics of tumor-initiating cells by inducing expression of CD44. In fact, it was reported that IL-4 administration strongly induces CD44 expression in PC3, but not in DU145 cells [74].…”
Section: Discussionmentioning
confidence: 99%
“…CD44 is also regulated by interleukin (IL)-4. IL-4 exposure (5 ng/ml) enhanced CD44 expression among prostate cancer cells PC3 [96]. Besides, krüppel-like factor 4 negatively modulated CD44 expression via binding to the CD44 promoter and disturbing gene transcription to restrict metastatic properties in human pancreatic ductal adenocarcinoma cells [97].…”
Section: Molecules and Pathways That Cd44 Regulatesmentioning
confidence: 99%
“…Interestingly, although CD44 serves as a biomarker of tumor-initiating cells with high expression of CD44, overexpression of CD44 cannot endow low CD44expressing cells with properties of tumor-initiating cells [106]. Besides, CD44 high /CD49 high subpopulation of prostate cancer PC3 cells displayed enhanced proliferative and clonogenic potential as compared to the CD44 low / CD49 low subgroup [96]. Debanjan Dhar's work has thrown light upon the pivotal role of CD44 in the tumorigenesis of hepatocellular carcinoma [108].…”
Section: Cd44 and Tumor Initiationmentioning
confidence: 99%
“…3D). To confirm that the PIM1‐induced stem cell signature is associated with a stemness state, we analyzed PIM1‐overexpressing cells for the enrichment of stem cell surface markers (CD24 (Weng et al , 2019), CD29 (Lawson et al , 2010; Vassilopoulos et al , 2014), and CD49B (Erb et al , 2018; Lawson et al , 2010). We demonstrate that PIM1 overexpression in PC3 cells induces stem cell surface markers CD29, CD49b, and CD24, suggesting that increased PIM1 expression is capable of inducing a stem cell‐like surface phenotype through in part regulating these gene changes (Fig.…”
Section: Resultsmentioning
confidence: 99%